How online review dimensions shape booking decisions: Evidence from Traveloka users in Surabaya - Rachel Maryam Ramadhani; Sheidy Yudhiasta (Jurnal Bisnis Mahasiswa, 2026)
Purpose – This study seeks to analyze the influence of electronic word-of-mouth (eWOM) dimensions on booking decisions for star-rated hotels in Surabaya via the Traveloka platform. Design/methodology/approach – This study adopts a quantitative approach with an explanatory research design. Data were obtained from 100 respondents selected through purposive sampling, specifically Traveloka users who have previously booked star-rated hotels in Surabaya. The data were then analyzed using multiple linear regression techniques with the assistance of SPSS software. Findings – The findings reveal that eWOM Quality, eWOM Quantity, and Sender’s Expertise collectively exert a significant influence on booking decisions. Partially, all variables also show positive and significant effects, with eWOM Quality identified as the most dominant variable. The model explains 69.8% of the variance in booking decisions. Research limitations – This study is limited to three eWOM dimensions and domestic tourists in Surabaya. Future research is suggested to include additional variables and broader research contexts to improve generalizability. Implications – The results emphasize the importance of effectively managing online reviews, as review quality, quantity, and source credibility are key factors in influencing consumer trust and booking decisions on online travel platforms. Originality – This study offers empirical insights into the collective influence of eWOM dimensions on hotel booking decisions within the context of Traveloka users in Surabaya.